Programa saúde na escola: a intersetorialidade saúde e educação - Dondoni, Daniele (2016)
The School Health Program (PSE) was established in the year 2007, and as an Interministerial Program of the Health and Education sectors, aimed to promote actions to improve the quality of life and the health and education conditions of children, adolescents and youngsters from the public school system in the country. For the achievement of its components I, II, III, the program envisioned the use of school space for the practices of promoting and preventing health, as well as building a culture of peace, citizenship development and qualification of Brazilian policies (BRAZIL, 2012a). This research therefore sought to answer the following question: What is the intention underlying the health and education intersectoriality in the School Health Program (PSE) proposed from the Booklets issued by the Ministries of Health and Education? In order to answer the research problem the following PSE Booklets were selected: Primary Care Booklet No. 24: Health in School (2009); Step by Step PSE - School Health Program: Weaving paths for intersectoriality (2011a); Health in School (2012e); Instructive Manual Health in School (2013c); and PSE Manager‟s Booklet (2015a). The methodological approach to the PSE Booklets‟ analysis involved reading to understand the categories of study related to the intention underlying the Health and Education Intersectoriality. With the research, it was possible to identify that the concept of Health and Education Intersectoriality in the PSE ranges from the process of Federal Management to the health and education actions carried out in schools. Intersectorial activities related to health and education required the study of the PSE and its relation with the concept of Health Promotion and the expanded and restricted concepts of health. Thus, it was concluded that although the Health and Education Intersectorial work approach in the PSE supports the practice of Health Promotion with an enlarged view, there is individual responsibility for incorporating health practices through the concepts of empowerment and autonomy, as recommended by the analyzed Booklets